The Influence of Transformational Leadership and Work-Life Balance on Organizational Citizenship Behavior with Job Satisfaction as an Intervening Variable: (Case Study on Employees of PT. Tunas Madukara Indah, Wonosobo Regency) - Hana Sabrina; M. Trihudiyatmanto; Heri Purwanto (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
Purpose - This study aims to determine the Influence of Transformational Leadership and Work Life Balance on Organizational Citizenship Behavior with job satisfaction as an Intervening variable at PT. Tunas Madukara Indah 2 Wonosobo. Design/methodology/approach - This study is a quantitative study. The sampling technique uses random sampling technique with a population of 360 employees and obtains a sample of 187 employees. This study uses an analysis tool, namely SmartPLS 4.1.0.9. Findings - Transformational Leadership has a negative effect on Organizational Citizenship Behavior, Work life balance has a positive and significant effect on Organizational Citizenship Behavior, Transformational Leadership has a positive and significant effect on Job Satisfaction. Work Life Balance has a positive and significant effect on job satisfaction. Job Satisfaction has a positive and significant effect on Organizational Citizenship Behavior. Job Satisfaction has a positive and significant effect in mediating the effect of Transformational Leadership on Organizational Citizenship Behavior. Job Satisfaction has a positive and significant effect in mediating the effect of Work Life Balance on Organizational Citizenship Behavior.